The analysis and classification of problems of environmental protection of the urbanized territory of Kazakhstan - Kenzhebekov, N.D.; Shelomentsev, A.G.; Kabdybay, А.К.; Zambinovа , G.K. (BUKETOV BUSINESS REVIEW, 2017)
In article the analysis and classification of the main problems of environmental protection of the urbanized territory of Kazakhstan are presented. Unevenness of emissions of the substances polluting the atmosphere departing from stationary sources across the territory of Kazakhstan is shown. The cities with high extent of pollution of atmospheric air are revealed, the main sources of pollution are defined. Dynamics of an index of pollution of the atmosphere in settlements of the Republic of Kazakhstan is estimated. The cities in which cases of high pollution and extremely high pollution in atmospheric air are recorded are allocated. The current assessment of use of water resources on the basis of the analysis of dynamics of a fence and losses of water, and also the main water consumers in a section of areas and cities of Kazakhstan is given. The main problems of rational use of natural resources are defined. Target indicators of the State program of water resources management are presented. The current situation in the field of education and utilization of municipal solid waste is assessed. The main problems in this direction, in particular management of thriftless dumps of municipal solid waste, withdrawal at the population of dangerous municipal solid waste are allocated. The analysis of dynamics of formation of industrial wastes is carried out, key industries education sources are defined. On the basis of the carried-out analysis classification of the environmental problems having significant effect on an ecosystem of the cities is presented and the factors constraining the solution of environmental problems and processes of greening of city economy are generalized.